How Digital Literacy, Big five Personalities, and Competence Shape Teaching Performance: Evidence from Madrasah Tsanawiyah Negeri in Kebumen - Sandra Della Rafika; Prasetyo Anton (STIE Amkop Makassar, 2025)
This study investigates the influence of digital literacy, The Big Five Personality traits, and teacher competence on teacher performance at Madrasah Tsanawiyah Negeri in Kebumen. Employing a quantitative approach with Structural Equation Modeling (SEM), the research analyzes data collected from 170 respondents. The findings reveal that digital literacy significantly affects teacher performance, with improved digital skills enhancing teaching effectiveness. Furthermore, The Big Five Personality traits, specifically traits such as conscientiousness and emotional stability, positively influence teacher performance. The results also show that teacher competence plays a crucial role in improving performance, especially in understanding student needs and developing effective teaching strategies. These findings suggest that enhancing teachers' digital literacy, fostering positive personality traits, and improving their competence can collectively improve their performance in educational settings. The study provides theoretical contributions by emphasizing the importance of these factors in shaping teacher performance and offers practical implications for educational institutions, recommending targeted interventions to boost digital literacy, support personality development, and improve teacher training.